The DIGITAL RELIGION: PRAKTIK KEAGAMAAN DALAM DUNIA DIGITAL KASUS AMERIKA SERIKAT: 1. Pendahuluan; 2. Metode Penelitian; 3. Hasil Penelitian, Pengaruh Teknologi Terhadap Ritual Keagamaan, Televangelisme di Amerika Serikat, Tantangan Teknologi dalam Komunitas Keagamaan Online, Relasi Antar Agama di Era Digital, Digitalisasi Pendidikan Agama; 4. Kesimpulan - Amiriyah Al-Achsanah, Mursyidah; Lailatus Sholikhah, Nur (Universitas Muhammadiyah Surabaya, 2025)
Abstract: This article discusses religious practices and education that occur in the United States in the digital era. As one of the pioneers in the development of digital technology, the United States is very interesting to explore. The encounter of religion with digital technology has led to a transformation in religious activities. This transformation includes many things from rituals and social activities. The scientific approach used by the author in writing this article is a qualitative approach. The literature study method is the method chosen by the author. To obtain research data the author quoted from literature, journal articles, books, news media websites, and survey institute websites. In this approach, the author analyzes written literacy sources to gain information and understanding of the topics discussed. This research clearly explains that digital era religious rituals package rituals online. For example, there is the phenomenon of digital holy books and prayer guides, online Sunday services, online recitations, and so on. Then the spread of religious messages through electronic media or televangelism over time develops and expands. Religious education is given little attention there because of the decline in the spirituality of the population. Although relations between religions have many challenges, there is sufficient broad access to moderation. Keywords: Digital Religion, Religious Practice, USA.